Application of InP/ZnSe/ZnS Quantum Dots in the Treatment of Experimental Antibiotic-Resistant Endophthalmitis in vivo - V. O. Ponomarev; V. N. Kazaykin; K. A. Tkachenko; A. S. Vokhmintsev; I. A. Weinstein; A. E. Zhdanov (Oftalʹmologiâ, 2023)
Purpose: modeling of experimental antibiotic-resistant endophthalmitis on laboratory animals model describing the interaction of quantum dots and a biological organism and its physicochemical and kinetic aspects.Material and methods. The object of the study is laboratory New Zealand rabbits (2 male, age 4 months, weight 3.5 kg). The inflammation inductor is the culture of Methicillin-Resistant Staphylococcus Aureus (MRSA). 1 mg/0.05 ml of vancomycin in combination with 0.5 μg (0.01 %)/0.05 ml by a solution of quantum dots InP/ZnSe/ZnS 660 was intravitreally administrated to the first rabbit. 1 mg/0.1 ml of vancomycin was intravitreally administrated to the second rabbit. Dynamic observation of the clinical process was performed daily by photo registration of the front segment and ultrasonic sonography.Results. The conjugate based on 1 mg/0.05 ml vancomycin coupled with 0.5 μg (0.01 %)/0.05 ml quantum dots InP/ZnSe/ZnS 660 demonstrated high anti-infectious activity against vancomycin-resistant MRSA. It was shown that the effect of the above solution on MRSA is described by the one-time ability of quantum dots by using electron microscopy. The presence of superoxide radicals O2–• generation in an aqueous solution of quantum dots under the action of blue light has also been proven by spectrophotometric method.Conclusion. Conjugates based on quantum dots can be considered as one of the promising directions of treatment of antibiotic-resistant endophthalmitis.